Treatment of experienced and naïve patients with hepatitis C: focus on telaprevir - D'Ambrosio R (Dove Medical Press, 2012)
Roberta D’Ambrosio, Alessio Aghemo, Massimo ColomboCentro A.M. e A. Migliavacca, First Division of Gastroenterology, Fondazione IRCCS Cà Granda Ospedale Maggiore Policlinico, Università degli Studi di Milano, Milan, ItalyAbstract: Telaprevir (TVR) is an orally available protease inhibitor of the hepatitis C virus that in association with pegylated interferon and ribavirin (PR) was shown to improve the rates of sustained virological response and potentially reduce treatment duration in adult patients with chronic hepatitis C genotype. Despite its robust activity in both treatment-naïve and experienced patients, the addition of TVR to PR is counterbalanced by increased costs and adverse events; moreover, there are still areas of uncertainty that regard treatment of patients with advanced liver disease, the role of patient stratification by genetic predictors, and the use/need for a lead-in phase with PR. Since TVR regimens have been associated with the risk of viral mutants that may cause treatment failure and jeopardize future therapeutic strategies with direct-acting antiviral agents, early stopping rules have been designed to protect patients with a poor virological response to TVR regimens against such a risk.Keywords: protease inhibitor, pegylated interferon, ribavirin